2020
DOI: 10.1002/fes3.203
|View full text |Cite
|
Sign up to set email alerts
|

Uptake prediction of ten heavy metals by Corchorus olitorius L. cultivated in soil mixed with sewage sludge

Abstract: This study was carried out to develop mathematical regression equations for predicting the uptake of selected heavy metals (HMs: Cd, Co, Cr, Cu, Fe, Mn, Mo, Ni, Pb, and Zn) by Corchorus olitorius L. cultivated in soil mixed with sewage sludge based on the concentration of these HMs in the soil–sludge mixture, soil organic matter (OM), and soil pH. The resultant regression equations reflected that the three soil factors were significant predictors for the uptake of the ten HMs in the plant tissues. Applying the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
(92 reference statements)
0
6
0
Order By: Relevance
“…This suggests that Fe concentration in the various vegetables was safe for consumption. However, In Pakistan, Nisa et al (2020), reported low Fe concentration in vegetables contrariwise, to the Fe concentration reported by Eid et al (2020), in Corchorus olitorius L. cultivated in Abha -Saudi Arabia.…”
Section: Level Of Heavy Metal Residue In Vegetablesmentioning
confidence: 69%
“…This suggests that Fe concentration in the various vegetables was safe for consumption. However, In Pakistan, Nisa et al (2020), reported low Fe concentration in vegetables contrariwise, to the Fe concentration reported by Eid et al (2020), in Corchorus olitorius L. cultivated in Abha -Saudi Arabia.…”
Section: Level Of Heavy Metal Residue In Vegetablesmentioning
confidence: 69%
“…The soils heavy metals content from three (3) different locations along Rivers Jakara and Getsi were presented in Table 5 and 6 (Zhou et al, 2019), lower soil pH and higher abundance of organic matter favour heavy metals uptake by crops Hou et al, 2019;Eid et al, 2020;Liu et al, 2020 andOuyang et al, 2020). Alkaline pH lowers heavy metals solubility (Swiatek et al, 2019), therefore alkaline soil retain heavy metals.…”
Section: Resultsmentioning
confidence: 99%
“…Since there is not much literature available relating to the establishment of regression models specifically for the absorption of metals by A. esculentus grown in media combined with varying sewage sludge concentrations, the obtained data were compared with studies that evaluated similar concepts using regression models pertaining to alternative crops. When judged against the tissues of A. esculentus in which Cd variability was 77.7-92.5%, Cd variabilities within the plant components for cucumber [1], barley [43], kidney bean [47], garden pea [48], Corchorus olitorius [49], Eruca sativa [50], and spinach [51] were 49-76%, 45-88%, 44-61%, 25-67%, 69-75%, 49-81%, and 83-88%, respectively. Bešter et al [44] used models to measure the impact of Cd in tomato and endive, which exhibited R 2 values of 41% and 90%, respectively.…”
Section: Discussionmentioning
confidence: 99%